A new biased estimator for the gamma regression model: Some applications in medical sciences. Issue 11 (3rd June 2023) - Akram, Muhammad Nauman; Amin, Muhammad; Qasim, Muhammad
Abstract: The Gamma Regression Model (GRM) has a variety of applications in medical sciences and other disciplines. The results of the GRM may be misleading in the presence of multicollinearity. In this article, a new biased estimator called James-Stein estimator is proposed to reduce the impact of correlated regressors for the GRM. The mean squared error (MSE) properties of the proposed estimator are derived and compared with the existing estimators. We conducted a simulation study and employed the MSE and bias evaluation criterion to judge the proposed estimator's performance. Finally, two medical dataset are considered to show the benefit of the proposed estimator over existing estimators.